Frizzled/PCP-dependent asymmetric neuralized expression determines R3/R4 fates in the Drosophila eye. - del Alamo, D.; Mlodzik, M. (Developmental Cell, 2006)
Planar cell polarity (PCP) is a common feature in many epithelia, reflected in cellular organization within the plane of an epithelium. In the Drosophila eye, Frizzled (Fz)/PCP signaling induces cell-fate specification of the R3/R4 photoreceptors through regulation of Notch activation in R4. Except for Dl upregulation in R3, the mechanism of how Fz/PCP signaling regulates Notch in this context is not understood. We demonstrate that the E3-ubiquitin ligase Neuralized (Neur), required for Dl-N signaling, is asymmetrically expressed within the R3/R4 pair. It is required in R3, where it is also upregulated in a Fz/PCP-dependent manner. As is the case for Dl, N activity in R4 further represses neur expression, thus, reinforcing the asymmetry. We demonstrate that Neur asymmetry is instructive in correct R3/R4 specification. Our data indicate that Fz/PCP-dependent Neur expression in R3 ensures the proper directionality of Dl-N signaling during R3/R4 specification.